1993
DOI: 10.1038/hdy.1993.107
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between the individual heterozygosity of parents and their offspring

Abstract: Specific formulations are derived for the correlation between the heterozygosity of a randomly mating parent and its offspring for a diallelic locus, and for the correlation when multiple loci are considered. The expected correlation is maximal, approaching r = 0.50, when allelic frequencies are highly asymmetric, and it is zero when the allelic frequencies are equal to 0.50. Parent-offspring correlations, up to a maximum of 0.50 for diallelic loci, indicate that levels of heterozygosity can respond to selecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
106
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(110 citation statements)
references
References 21 publications
3
106
1
Order By: Relevance
“…This increase in genetic diversity over time may have been in part reinforced by the moderate level of narrow‐sense heritability of heterozygosity (sensu Mitton, Schuster, Cothran, & deFries, 1993) found in our studied blue tit populations ( h 2  = 0.3; García‐Navas et al., 2009) as well as a result of positive selection on heterozygosity for many other fitness‐related traits, including breeding performance (García‐Navas et al., 2009), resistance to parasites (Ferrer et al., 2014), and sexual selection (Ferrer et al., 2015; García‐Navas et al., 2009) (for other blue tit populations, see Foerster et al., 2003; Olano‐Marin, Mueller, & Kempenaers, 2011a; Olano‐Marin, Mueller, & Kempenaers, 2011b). Our results are thus in agreement with previous studies carried out in bottlenecked populations where selection against homozygotes is suggested as a possible mechanism for the maintenance or increase in heterozygosity over time (Bensch et al., 2006; Forcada & Hoffman, 2014; Kaeuffer et al., 2007).…”
Section: Discussionmentioning
confidence: 69%
“…This increase in genetic diversity over time may have been in part reinforced by the moderate level of narrow‐sense heritability of heterozygosity (sensu Mitton, Schuster, Cothran, & deFries, 1993) found in our studied blue tit populations ( h 2  = 0.3; García‐Navas et al., 2009) as well as a result of positive selection on heterozygosity for many other fitness‐related traits, including breeding performance (García‐Navas et al., 2009), resistance to parasites (Ferrer et al., 2014), and sexual selection (Ferrer et al., 2015; García‐Navas et al., 2009) (for other blue tit populations, see Foerster et al., 2003; Olano‐Marin, Mueller, & Kempenaers, 2011a; Olano‐Marin, Mueller, & Kempenaers, 2011b). Our results are thus in agreement with previous studies carried out in bottlenecked populations where selection against homozygotes is suggested as a possible mechanism for the maintenance or increase in heterozygosity over time (Bensch et al., 2006; Forcada & Hoffman, 2014; Kaeuffer et al., 2007).…”
Section: Discussionmentioning
confidence: 69%
“…Although we have a quantitative understanding of the heritability of heterozygosity for cases of two alleles and no inbreeding (Mitton et al, 1993), most empirical studies that reported parent-offspring correlations in heterozygosity have used multiallelic genetic (e.g., microsatellite) markers. Additionally, although point mutations in coding DNA usually lead to biallelic single-nucleotide polymorphisms, many fitness-relevant genes will carry multiple mutations leading to multiple haplotypes (e.g., immune genes).…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical studies have shown that heterozygosity is heritable when allele frequencies are unequal (Borgia, 1979;Mitton et al, 1993;Neff and Pitcher, 2008), and a number of empirical studies have reported parent-offspring correlations in heterozygosity itself (Cothran et al, 1983;Mitton et al, 1993;Richardson et al, 2004;Hoffman et al, 2007;García-Navas et al, 2009;Oh, 2009;Thoß, 2010;Thonhauser et al, 2014), or inferred them from a parent-offspring correlation in inbreeding coefficients (Reid et al, 2006). Although the presence of substantial heritability of heterozygosity has been formally shown for two-allelic loci more than two decades ago (Mitton et al, 1993), this is not well known among evolutionary biologists (e.g., Coulson and Clegg, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…However, the choice would then focus on relative song characteristics and depend on the genotype of the individual female. Females can increase the heterozygosity of their offspring not only when mating with genetically dissimilar males but also when mating with more heterozygous males (Mitton et al 1993). A male could indicate his heterozygosity through absolute values of song rate or song diversity.…”
Section: Discussionmentioning
confidence: 99%